Leveraging TERM for Sustainable Entrepreneurial Growth in Higher Education Institutions - Jati Nugroho; Rif’ah Dwi Astuti; Sri Wahyuni; Saptianing; Makmun Riyanto (Cita konsultindo, 2025)
Higher education institutions play a pivotal role in shaping the next generation of entrepreneurs. This article explores how the Techno-Entrepreneurial Relationship Marketing (TERM) model can be leveraged to foster sustainable entrepreneurial growth among students. Drawing on a mixed-methods study involving 150 student entrepreneurs in Central Java, the research examines the impact of TERM on marketing performance and competitive advantage. The study highlights the critical role of digital tools, entrepreneurial orientation, and proactive customer engagement in building resilient, market-oriented businesses. The findings reveal that students who effectively utilize digital technologies such as social media, customer relationship management (CRM) systems, and data analytics achieve superior marketing performance, customer loyalty, and long-term business sustainability. Moreover, the research emphasizes the importance of integrating TERM into educational curricula to prepare students for the challenges of a rapidly evolving digital economy. This paper concludes with practical recommendations for educators, policymakers, and student entrepreneurs on how to incorporate TERM into business training programs, thereby enhancing the digital competitiveness and entrepreneurial resilience of future business leaders. These insights are particularly relevant for institutions seeking to develop the next generation of innovative, tech-savvy entrepreneurs.